P PHILOSOPHY OF LIVING ETHICS AS A NEW SYSTEM OF KNOWLEDGE - Кадникова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Тhe article examines the formation of a new system of knowledge in the Living Ethics teaching.